Design of a single phase AC-AC converter - Khan, Md. Imtiaz; Ahad, Abdul; Islam, Kamrul (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.